SEKOLAH INKLUSI JENJANG PENDIDIKAN ANAK USIA DINI DI BATU SOPANG KALIMANTAN TIMUR - Dwi Aprilyani Saragih; Prima Widia Wastuty; Bani Noor Muchamad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Early childhood education is a crucial educational stage which is the optimal-not-optimal background for human development in the future. Early childhood education is also an instrument that every child with different abilities has the right to get and is given the same opportunity to recognize, shape and hone their special abilities. Inclusive early childhood education with universe-based learning methods is a form of learning that is easy to understand in everyday life which also has thematic learning forms so that it can stimulate children's cognitive holistically. PAUD using the Nature School method is also designed to use an architectural program approach in the process. The design includes a natural material base as a learning feature and is followed by a mass arrangement that responds to the site and activity, circulation flow, visual form of the building, color and material.